1998
DOI: 10.1191/026765898676398460
|View full text |Cite
|
Sign up to set email alerts
|

The role of phonemic awareness in second language reading

Abstract: This study investigates the effects of disparate L1 (first language) alphabetic experience on L2 (second language) phonemic awareness and decoding among ESL (English as a Second Language) readers with alphabetic and nonalphabetic L1 orthographic backgrounds. It was hypothesized that amount of L1 alphabetic experience is causally related to the development of L2 phonemic awareness and decoding skills. The specific objectives were threefold: to compare varying aspects of phonemic awareness among Chinese and Kore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 35 publications
3
48
2
Order By: Relevance
“…By contrast, students of an alphabetic language background may rely on predictable orthography-tophonology correspondence in L1 word learning. There is evidence that Chinese learners of English are different from students of an alphabetic L1 background in phonetic awareness and decoding processes (Koda, 1998). The different strategy in phonemic decoding and word learning may have important implications for the development of reading fluency and reading comprehension among Chinese EFL readers.…”
Section: The Influence Of L1 Orthography On L2 Readingmentioning
confidence: 99%
“…By contrast, students of an alphabetic language background may rely on predictable orthography-tophonology correspondence in L1 word learning. There is evidence that Chinese learners of English are different from students of an alphabetic L1 background in phonetic awareness and decoding processes (Koda, 1998). The different strategy in phonemic decoding and word learning may have important implications for the development of reading fluency and reading comprehension among Chinese EFL readers.…”
Section: The Influence Of L1 Orthography On L2 Readingmentioning
confidence: 99%
“…In fact, Korean letters were scientifically developed to fit the Korean language, which is syllabic. Consequently, Korean-English bilingual students tend to more easily recognize symbol-sound correspondence in Korean than in English (Koda, 1998;Shin, 2005 Many children in the United States are living in an environment where English literacy and oral language are highly prized and where children are provided not only with English oral language input but also instruction in English literacy on a scale that seems nearly impossible to match with spoken heritage language and literacy input. This exposure to English oral language and English literacy, and the potential benefits of this valuable linguistic code (Wong-Fillmore, 1991a), appears to override individuals' and families' value on spoken home language and literacy retention.…”
Section: The Child's Perspective Attitude and Linguistic Behaviormentioning
confidence: 98%
“…For example, he exhibited an increased understanding that: 1) letters are written from left to right and top to bottom; 2) letters should be in an imaginary square box; 3) letters usually are written to allow spaces between words, but not in all cases; and 4) Korean letters are not capitalized (Koda, 1998).…”
Section: The Child's Perspective Attitude and Linguistic Behaviormentioning
confidence: 99%
“…Inasmuch as the critical contrast between alphabetic and logographic literacy lies in the relative reliance on phonological and graphic information during decoding, in these studies, L2 stimulus words were manipulated either phonologically (e.g., blocking phonological information by replacing words with unpronounceable symbols, such as ; Koda, 1990) or graphically (e.g., creating visual distortion by replacing real words, such as "read," with their case altered version "ReAd"; Akamatsu, 1999), and the magnitude of the manipulation employed was compared among L2 learners with contrasting L1 backgrounds. Their data demonstrated that diverse L2 learner groups responded differently to the two types of manipulation (Green & Meara, 1987;Koda, 1998;Akamatsu, 1999) and that the reported differences were identifi able with the orthographic properties of the participants' respective fi rst languages (Koda, 1990(Koda, , 1993Ryan & Meara, 1991). Viewed together, these fi ndings suggest that previously acquired L1 mapping skills are involved in L2 reading development, systematically altering L2 decoding behaviors.…”
Section: L1 Orthographic Knowledgementioning
confidence: 99%